Comparison of acute and chronic exercise effects in the lipid droplets topography skeletal muscle, following high and low-fat diet in mice - Triantou, Vasiliki (2015)
In the modern world, diet patterns high on lipids, sedentary lifestyle and obesity contribute all in the development of metabolic syndrome, which in turn can lead to type 2 diabetes. All the excess fats, that the majority of the population consumes nowadays, are stored as ectopic fat, particularly in the skeletal muscle, a tissue beyond doubt insulin-sensitive. Physical activity has been proposed according to various studies to be the most drastic factor, which can induce changes in skeletal muscle lipid metabolism,as well as different diet models. We hypothesized that different exercise patterns and diet-changes can alter the spatial arrangement in lipid droplets (LDs) in different skeletal muscle fiber types of C57BL/6J mice. Muscle samples from gastrocnemius were collected from 8 groups: sedentary controls fed with a high-fat (HFD, n=10), or a low-fat diet (LFD, n=10), chronic exercise group fed with a high-fat (HFDR, n=10) or a low-fat diet (LFDR, n=10) and acute exercise group that either killed immediately after exercise or 6 hours later following a high-fat (HFD0, n=7 or HFDR6, n=7) or a low-fat diet (LFDR0, n=7 or LFDR6, n=7). Then immunohistochemistry and laser confocal microscopy were used, followed by image analysis. Fiber type LD size showed a significant difference between all groups, apart from the chronic exercise group fed with the low-fat diet and the acute exercise group fed with the high-fat diet and sacrificed 6 hours after exhaustion. Fiber type LD density showed a very significant difference(P<0.001) between all groups. It seems that physical activity with or without the highfat diet, induced changes in size and density of LDs, meaning that those two factors exercise and diet play a critical role in the prevention of metabolic syndrome later on. A precise comprehension of metabolic pathways participating in obesity and metabolic syndrome reinforces the worldwide effort of diminishing or totally eliminate them.